Peran Kontrol Diri Sebagai Moderator Pengaruh Social Comparison Terhadap Fear Of Missing Out Pada Pengguna Media Sosial - Rizal, Irfani; Herawaty, Yulia (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2025)
The use of social media is currently increasing, the habit of using one of the social media has an impact on the fear of being left behind or called the fear of missing out on social media users. This study fills the research gap in the psychological literature by validating the influence between social comparison and Fomo in the presence of self-control as a moderator. The purpose of this study is to look at the role of self-control as a moderator variable between the influence of social comparison on Fomo among 281 social media users. The population in this study were students who used social media aged 19-24 years. The measuring instruments used are the Fomo scale, social comparison and self-control. The data processor used is the Structural Equation Model (SEM) path analysis method with the Partial Least Square (PLS) method. The results of the analysis show that social comparison has an influence on fomo, self-control affects fomo and self-control is able to moderate the influence of social comparison on fear of missing out.